Applications of diamond-like carbon coatings - Zia, Abdul Wasy (Hoboken, New Jersey : Wiley, 2025)
An incisive guide to diamond-like carbon (DLC) coatings and their contemporary applications In Applications of Diamond-like Carbon Coatings, distinguished researcher Dr. Abdul Wasy Zia delivers an insightful and up-to-date discussion of the latest advancements in new and non-conventional applications of diamond-like carbon (DLC) coatings. The editor explains the transformation of typical topics into advanced applications of DLC, including tribology for future transportation solutions, green lubrication, invasive implants, MEMS, optical devices, and more. The book also details advanced and contemporary trends in DLC coatings, like material informatics involving artificial intelligence and machine learning, and new, net-zero applications, including energy storage batteries. Readers will also find: A thorough introduction to applications of DLC coatings in mechanics, transportation, medicine, and electrical and optical device manufacture Comprehensive explorations of emerging trends in DLC coatings, including green energy, data-centric approaches, textile and plastics, and carbon circularity from DLC coated products Practical discussions of how small and medium industries can design and develop DLC coatings for broad engineering applications Complete treatments of the benefits and opportunities presented by DLC coating applications Perfect for postgraduate students and researchers with an interest in DLC coatings, Applications of Diamond-like Carbon Coatings will also benefit scholars and instructors in academia, technical managers, scientists, engineers, and corporate research and development professionals with backgrounds in chemistry, materials science, polymer chemistry, and physical chemistry.
Keywords: Thin Films, Surfaces & Interfaces; Hydrogen, Batteries & Fuel Cells; Solid Mechanics; diamond-like carbon; DLC coatings; dlc coating; Carbon; diamond-like carbon coating applications; diamond-like carbon coating products; diamond-like carbon coating trends; diamond-like carbon coatings in industry; diamond-like carbon coating deposition; PVD; PECVD; Plasma deposition; Thin films; Surface Coatings; Interface; Tribology; Friction; Wear; Green lubrication; Healthcare; Biomedical; Implants; Orthodontics; Electronics; MEMS; Optical devices; Sensors; Textiles; Plastics; Energy Storage Batteries; Circular Economy; NetZero; Electronic books